Italo Calvino’s Invisible Cities: translation analysis and interpretive issues - Motisi, Anna (Estudios de Traducción, 2022)
This paper aims to emphasize the importance of interpretation in the translation process, the implications deriving from it, as well as their effect on the reader and the way they affect his or her reception and cultural use of the text. This subject matter will be examined through one of Italo Calvino’s best-known works, more specifically The Invisible Cities (translated by William Weaver). This is a work that can be ascribed to one of the branches of travel literature, namely the imaginary voyage, and that can be read as a sort of philosophical vademecum. Precisely because of its nature, it can undoubtedly be considered a text characterised by a structure, a style and a language that make it susceptible to different interpretations.In the translation analysis of this work, the focus will be on how translation can sometimes move away from the so called intentio operis that is, from interpretation in semiotic terms, from what the work wants to communicate on the level of signification, expressing it through its intrinsic textual coherence (Eco, 1990). Specifically, through the examination of certain stylistic, grammatical and lexical choices made by the translator, some portions of the text will be highlighted in which the construction of the meaning differs from that of the source language, thus distorting the textual cooperation whose protagonist is the reader (Eco, 1979).